Anti-Immune Strategies of Pathogenic Fungi - Marcos, Caroline M.; de Oliveira, Haroldo C.; de Melo, Wanessa de Cássia M. Antunes; da Silva, Julhiany de Fátima; Assato, Patrícia A.; Scorzoni, Liliana; Rossi, Suélen A.; de Paula e Silva, Ana C. A.; Mendes-Giannini, Maria J. S.; Fusco-Almeida, Ana M. (Frontiers in Cellular and Infection Microbiology, 2016)
Pathogenic fungi have developed many strategies to evade the host immune system. Multiple escape mechanisms appear to function together to inhibit attack by the various stages of both the adaptive and the innate immune response. Thus, after entering the host, such pathogens fight to overcome the immune system to allow their survival, colonization and spread to different sites of infection. Consequently, the establishment of a successful infectious process is closely related to the ability of the pathogen to modulate attack by the immune system. Most strategies employed to subvert or exploit the immune system are shared among different species of fungi. In this review, we summarize the main strategies employed for immune evasion by some of the major pathogenic fungi.